Promoting ‘testicular awareness’: Co‐design of an inclusive campaign using the World Café Methodology - Mohamad M. Saab; Varsha N. Shetty; Megan McCarthy; Martin P. Davoren; Angela Flynn; Ann Kirby; Steve Robertson; Gillian W. Shorter; David Murphy; Michael J. Rovito; Frances Shiely; Josephine Hegarty (Health Expectations)
Abstract Introduction Testicular cancer is the most common cancer in men aged 15–44 years in many countries. Most men with testicular cancer present with a lump. Testicular symptoms are more likely to occur secondary to benign diseases like epididymo‐orchitis, a common sexually transmitted infection. Gender and sexual minorities are at an increased risk of testicular diseases and health disparities. The aim of this study was to co‐design an inclusive community‐based campaign to promote testicular awareness. Methods This study uses the World Café methodology. Participation was sought from Lesbian, Gay, Bisexual, Transgender and Queer+ friendly organisations, testicular cancer survivors, health policy makers, media and marketing experts and graphic designers. Participants engaged in three rounds of conversations to co‐design the campaign. Data were collected using drawing sheets, artefact cards, sticky notes, coloured markers and a voice recorder. Deductive thematic analysis was conducted. Results Seventeen individuals participated in the study. Six themes emerged from the analysis as follows: (i) online communication; (ii) offline communication; (iii) behavioural targeting and education; (iv) campaign frequency and reach; (v) demographic segmentation; and (vi) campaign identity. The use of social media for campaign delivery featured strongly in all conversations. Participants also recommended offline communication using posters and radio/television advertisements to scale up the campaign and achieve wider reach. Advertisements to overcome embarrassment surrounding testicular health were particularly recommended. Participants emphasised that campaign delivery must be dynamic whilst ensuring that the health‐promoting messages are not diluted or lost. They stressed the importance of being inclusive and tailoring the campaign to different age groups, gender identities and sexual orientations. Conclusions Study recommendations will be used to design and deliver the campaign. Future research will be needed to evaluate the feasibility, acceptability, cost and effect of the campaign on promoting testicular awareness and early detection of testicular diseases. Patient or Public Contribution A participatory research approach was used to co‐design the campaign with members of Lesbian, Gay, Bisexual, Transgender and Queer+ (LGBTQ+) friendly organisations, LGBTQ+ student bodies, LGBTQ+ staff networks, LGBTQ+ sports clubs, men's health organisations, testicular cancer survivors, health policy makers, media and marketing experts and graphic designers.